2005
DOI: 10.1007/s11230-004-1373-x
|View full text |Cite
|
Sign up to set email alerts
|

A new entomopathogenic nematode, Steinernema robustispiculum n. sp. (Rhabditida: Steinernematidae), from Chumomray National Park in Vietnam

Abstract: Steinernema robustispiculum n. sp. (Rhabditida: Steinernematidae) was isolated from woodland in Chumomray National Park, Sason, Sathay, Kontum, Vietnam. Its morphology, morphometrics, cross-hybridisation and the ITS-rDNA sequence analysis revealed that S. robustispiculum clearly differs from other known Steinernema spp. As in the cases of S. intermedium (Poinar, 1985), S. robustispiculum has very robust spicules, but it can be distinguished by the longer tail of the infective juvenile, lower E%, shorter spicul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Surveys carried out in Vietnam revealed the presence of already described and some new species. S. tami (Luc et al, 2000), S. loci (Phan et al, 2001a), S. sangi (Phan et al, 2001a), S. thanhi (Phan et al, 2001b), S. robustispiculum (Phan et al, 2005), S. backanense (Phan et al, 2006a, b), S. cumgarense (Phan et al, 2006a, b), S. eapokense (Phan et al, 2006a, b), S. sasonense (Phan et al, 2006a, b), and S. huense (Phan et al, 2014) are some species of Steinernematids recorded from Vietnam. Among heterorhabditids, H. baujardi (Phan et al, 2003) has been found new to this country.…”
Section: Vietnammentioning
confidence: 99%
“…Surveys carried out in Vietnam revealed the presence of already described and some new species. S. tami (Luc et al, 2000), S. loci (Phan et al, 2001a), S. sangi (Phan et al, 2001a), S. thanhi (Phan et al, 2001b), S. robustispiculum (Phan et al, 2005), S. backanense (Phan et al, 2006a, b), S. cumgarense (Phan et al, 2006a, b), S. eapokense (Phan et al, 2006a, b), S. sasonense (Phan et al, 2006a, b), and S. huense (Phan et al, 2014) are some species of Steinernematids recorded from Vietnam. Among heterorhabditids, H. baujardi (Phan et al, 2003) has been found new to this country.…”
Section: Vietnammentioning
confidence: 99%
“…Most of entomopathogenic nematodes previously were unknown and their comprehensive studies based on morphological and molecular characterization as well as conducting some cross breeding tests allowed imaging a picture of the biodiversity of EPN in Vietnam [7,[9][10][11][12]. Concurrently with taxonomy works, the pathogenicity tests based on the indigenous isolates were obtained with Galleria mellonella and then with some insect pests to evaluate the potential of indigenous isolates for biological control.…”
Section: Entomopathogenicmentioning
confidence: 99%
“…Surveys of EPNs and symbiotic bacteria in the national parks have resulted in several new records in Thailand [ 18 , 19 , 20 ]. In addition, at least two new species of EPNs were isolated from national parks in Vietnam [ 21 , 22 ]. The national parks in Thailand are defined as areas that contain vast natural resources of ecological importance or unique beauty, or that possess flora and fauna of special importance.…”
Section: Introductionmentioning
confidence: 99%